The Culture of Speech in Cross-Cultural Communication - Tomash Vrabel; Vrábely Tamás; Врабель Томаш (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-Valerij Padjak, 2013)
Abstract. The article deals with developing the culture of speech of students studying crosscultural communication. The author singles out the components that hinder and I or enhance the mastery of communication in cross-cultural context. The relation of the notion of speech culture to idiomaticity of speech as well as to communication culture is elucidated. Communication culture is viewed as not only the ability to use cultural concepts in speech; it is based on following all the rules of speech culture, necessarily includes the knowledge of etiquette, strategies and tactics of behaviour in situations of everyday and professional communication. Speech culture, therefore, is determined by the linguistic awareness of a person. By studying peoples culture and speech we can determine their language awareness and the level of maturity of their language personality.
Оволодіння культурою мовлення в іншомовному оточенні
https://opac3.brff.monguz.hu:443/hu/record/-/record/157029
https://www.kmf.uz.ua/hun114/letoltes/acta/ActaAcBereg2013_2.pdf
Keywords: cross-cultural communication; speech culture; communication culture; idiomaticity of speech; norm; stylistic norm; linguistic awareness